Seasonal changes in the ovaries of three species of Siluriform fish: comparison of three species in a subtropical Argentinean environment - Romero, Nélida Marcela (2010)
The Siluriforms are a diverse, widely distributed group of Ostariophysi fish, with their greatest diversity in the tropical and subtropical regions. The order includes an important group of species of small size, relevant in the trophic nets of rivers and streams of different magnitudes. In the present work, we analyzed the seasonal changes in the ovaries of small-sized Siluriforms from rivers and streams in Valle de Lerma, Salta Province, Argentina. Seasonal samplings were carried out from 1995 to 2004 in four different environments. The specimens collected were fixed and measured, and the gonads were removed for histological processing. The species selected were Corydoras paleatus, Trichomycterus spegazzinii and Heptapterus mustelinus. The parameters analyzed were the condition factor (K), the gonadosomatic index (GSI), ovocitary frequency, fecundity, minimum size at sexual maturity, and macro and microscopic characteristics of the gonads throughout the seasons. The spawning season was determined for each species. The histological changes in the different stages of maturity of the gonads are similar among these species. They are partial spawners; the spawning season extends from early spring to mid summer for T. spegazzinii and H. mustelinus, whereas C. paleatus spawn throughout the year, with peaks in summers.